ABILITY OF READING COMPREHENSION USING COOPERATIVE SCRIPT FOR NON-ENGLISH DEPARTMENT - Hidayatur Rohmah; Khusnul Khotimah (ELT Worldwide: Journal of English Language Teaching, 2020)
The objectives of this study are implementation, and evaluation using Cooperative Script method in reading comprehension. It also to determine whether or not there is an increase in reading comprehension results using the Cooperative Script method. This research referred as qualitative research, which is an action thought on a particular object. The type of this research is Classroom Action Research. Classroom action research is a digestion of learning activities in the form of an action, which is deliberately raised and occurs in a class together. The process of reading comprehension in this study uses the Cooperative Script method, which consists of 2 cycles of 5 meetings. The first cycle consisted of two meetings and the second cycle of two meetings, one meeting was used for the pre-test. In planning, the researcher compiles a learning implementation plan, makes learning media compile an observation instrument to observe students in learning activities. The process of implementing evaluation in this learning is carried out at the end of each cycle. The assessment is carried out to determine the ability of students' reading comprehension in using the methods that have been applied. The success rate in each cycle has increased, starting from the pre-test which increased on average 45 in cycle I to 61.10 then increased again in cycle II to 72.3. From the results of the assessment it can be proven that the application of the Cooperative Script method can improve students' reading comprehension.